Teaching and learning assistant: classroom questioning web application (CQWA) - Ali Mohammed, Salam (2014)
Nowadays, using software technologies has become a significant component in the universities around the world. Software technologies facilitate many kinds of processes, such as providing services for teaching and learning. The major aim of any university is teaching and educating. The classroom is the most popular environment that is generally used by universities for sharing skills. The interaction between the instructors and students in the classroom makes teaching and learning process more advantageous. One of the common and beneficial ways of interaction is performed through questioning and answering activities. However, the majority of students find it difficult to ask questions in front of their colleagues. Several software services have been used by universities in the classroom, but these services do not provide students with any option to ask questions. In addition, some of these applications are not created for educational purpose. Therefore, the aim of this project is to provide students and instructors with an application to enhance classroom interaction. Moreover, this application is created only for classroom activities, which is a web application that can be used by universities to increase the students‟ engagement in the classroom. Students can use it to send questions during the class sessions, and lecturer can manage all the received questions. This dissertation first explores the motivation behind developing this application, and then how the application has been developed, implemented and test. After that, the conclusion reached along the limitations, and future works that may enhance the performance of the application.